Numerical models of fracture dynamics - Bratov, Vladimir Andreevich (Computational Continuum Mechanics, 2009)
This paper is concerned with the problems related to the embedment of an incubation time brittle fracture criterion into finite-element computational schemes. Several examples of how the incubation time fracture criterion can be used as a fracture condition in finite element computational schemes are given. Applicability of the approach for prediction of initiation, propagation and arrest of dynamic fracture is demonstrated.